A Comparison of Transradial and Transfemoral Approaches for Percutaneous Coronary Intervention in Elderly Patients Based on a Propensity Score Analysis. (May 2015) - He, Pei-Yuan; Yang, Yue-Jin; Qiao, Shu-Bin; Xu, Bo; Yao, Min; Wu, Yong-Jian; Yuan, Jin-Qing; Chen, Jue; Liu, Hai-Bo; Dai, Jun; Tang, Xin-Ran; Wang, Yang; et al.
The transradial approach (TRA) has been used as access site for percutaneous coronary intervention (PCI) for years. However, no large sample study has evaluated the effect of TRA in elderly patients. A total of 1098 elderly patients (age ≥ 75 years) who underwent PCI by TRA or transfemoral approach were recruited. A 1:1 matched propensity score analysis was performed to minimize bias. The rates of major adverse cardiovascular events that included death, myocardial infarction (MI), and target vessel revascularization during hospitalization (1.3% vs 6.6%, P = .014) and at 1-year follow-up (6.0% vs 13.9%, P = .019) were significantly lower in the TRA group. Transradial approach was also associated with lower rates of in-hospital MI (1.3% vs 5.3%, P = .046), access-site complications (3.3% vs 9.9%, P = .018), and major bleeding (1.3% vs 5.3%, P = .046). In conclusion, TRA showed better safety in elderly patients; it should be considered as a preferred route for elderly patients.